El Excentrico, 1972-09-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
September 5, 1972 [5 de septiembre de 1972]. No volume or issue number. Cover has a photograph of actor Gustavo Rojo to advertise Hank Coca's Furniture Discount House in San Jose, California.